2022
DOI: 10.3390/children9081125
|View full text |Cite
|
Sign up to set email alerts
|

Let Us Avoid a ‘Myopic View’ in Times of COVID-19

Abstract: The COVID-19 pandemic has affected people from almost all facets of life and it’s impact is extremely palpable among students. In this review paper, we discuss about the risk factors for myopia progression that were exacerbated by the pandemic, which are supported by evidence from studies published recently. It is imperative that measures are put in place to address the rising incidence of myopia so as to prevent the impending myopia pandemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 39 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…Increased screen time and reduced outdoor time are both known risk factors for myopia progression. [ 3 4 ]…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Increased screen time and reduced outdoor time are both known risk factors for myopia progression. [ 3 4 ]…”
mentioning
confidence: 99%
“… Reduce near work and accommodation for home-based learning and leisure: Use long viewing distance devices such as projectors and television screens instead of tablets and smartphones as some studies have reported that shorter viewing distances may cause more significant myopia progression than long viewing distance devices due to the increased accommodation effort required[ 2 3 4 5 ] Ensure adequate breaks in between video conferencing as there is increasing evidence to suggest that the intensity of near work, i.e., sustained reading at closer distance with fewer breaks, may be more important than the total hours of near work contributing to myopia progression[ 4 ] Encourage good reading habits such as reading in an adequately lit room and ensuring a good distance between books/computer screens from the eyes[ 4 ] Use audio media such as audiobooks and podcasts to replace screen time where feasible Reduce time spent on digital devices such as video gaming by setting limits on screen time or substituting them with activities such as physical exercises, helping with household chores, arts and crafts, baking/cooking, listening to radio, and free play. Spend more time outdoors and place study tables near windows, on balconies and roof terraces, and in gardens and car porches whenever possible Continue monitoring of myopia and education of patients and parents through teleconsultation Institute myopia-control interventions earlier and more aggressively when indicated.…”
mentioning
confidence: 99%
See 1 more Smart Citation